Cell-based Therapy: A Good Option for Retrieving Nephropathy Induced by Cyclosporine - Hanaa H. Ahmed (Journal of Global Pharma Technology, 2016)
Objective: The main goal is to address the role of mesenchymal stem cells derived from bone marrow (BM-MSCs) and adipose tissue (AD-MSCs) in mitigation of cyclosporine A (CsA)-induced nephropathy in rats. Methods: Isolation and propagation of MSCs from both sources were performed and the cells were recognized by the microscopic appearance and estimation of specific surface antigens (CD90, CD105 and CD45) using flow cytometry. In this study 40 adult male rats were distributed into 4 groups; (1) control group, (2) CsA group, (3) BM-MSCs group and (4) AD-MSCs group. Two month after stem cell infusion, urea and creatinine serum levels were estimated. Also, serum levels of MCP-1, NF-κB, nephrin and NAG activity were evaluated. Also, histopathology of kidney sections was carried out. Results: Microscopic photo documentation and CD surface markers proved that the isolated cells have typical characteristics of MSCs. The outcomes of the in vivo study indicate the beneficial effect of BM-MSCs and AD-MSCs in kidney restoration as manifested by the significant blunting in serum urea, creatinine, MCP- 1, NF-κB levels and the significant inhibition of serum NAG paralleled by the significant increase of serum nephrin level and GFR. These findings were also appreciated by the histopathological observation of kidney tissue sections as the cell therapy elicited marked betterment in the structural organization of kidney tissue. Conclusion: This study provides great evidence favoring the significant role of MSCs, particularly isolated from AD, in retrieving experimental nephropathy induced by cyclosporine. The efficiency of MSCs could be ascribed to their immunomodulatory effect, anti-inflammatory and anti-apoptotic property.Keywords: Mesenchymal stem cells, Nephropathy, Inflammation, Apoptosis, Rats.